Computational Methods and Experimental Measurements XVII 2015
DOI: 10.2495/cmem150341
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modelling of the resistive heating of disposable molecular diagnostics devices

Abstract: We present a finite element model for the simulation of the resistive heating of microchannels in disposable molecular diagnostics devices by means of various resistive heating elements, and demonstrate the validity of this model through experiments. Polyimide etched foil heaters and heaters based on positive temperature coefficient (PTC) ceramics could be simple, cost-efficient and robust means of heating disposable Lab-on-a-Chip devices that depend on maintaining a given temperature range in the channels for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Manufacturer specifications state the resistance of the heating element as 70.2Ω, however, in a previous work we measured initial resistance to be 76.38 ± 0.37Ω [3].…”
Section: Electrical Characterization Of Heating Elementmentioning
confidence: 87%
See 1 more Smart Citation
“…Manufacturer specifications state the resistance of the heating element as 70.2Ω, however, in a previous work we measured initial resistance to be 76.38 ± 0.37Ω [3].…”
Section: Electrical Characterization Of Heating Elementmentioning
confidence: 87%
“…Earlier we demonstrated finite element models for passively regulated (self-regulating) and non-regulated resistive heating for temperature control in disposable Point-of-Care rapid tests using commercially available resistive heating elements [3]. In this paper, we propose a finite element model for active temperature control of disposable molecular diagnostics devices, as well as demonstrate a mini-thermostat application based on open-source (Arduinocompatible) hardware for various isothermal nucleic acid amplification assays.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of the etched foil heating element was considered constant in the temperature range studied, and was measured at 76.38 ± 0.37 Ω [ 20 ], rather than the 70.2 Ω [ 33 ] disclosed by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…In previous works, we investigated finite element modelling as a tool for the thermal analysis of various commercially available heating elements [ 20 , 21 , 22 ]. In this work, we demonstrate the process by which commercially available resistive heating elements can be evaluated for use as temperature control solutions for NINAAT systems.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, we demonstrated the methodology for simulated and experimental thermal analysis of LoC NAAT systems with integrated temperature control based on commercially available electrical heating elements [ 30 , 31 , 32 , 33 ]. We compared the performance of a commercially available self-regulating heating element to a thermostat-regulated etched foil heating element in LoC NAAT prototypes and concluded that self-regulating heating was the favorable option for disposable instrument-free LoC NAAT devices [ 33 ].…”
Section: Introductionmentioning
confidence: 99%